PERTUKARAN SOSIAL DALAM KOMUNIKASI PEMBELAJARAN EFEKTIF PENGAJAR TERHADAP ANAK JALANAN PADA KOMUNITAS PEDULI ANAK JALANAN (KPAJ) - Alam, Nur; Bahfiarti, Tuti; Fatimah, Jeanny Maria (JIKE : Jurnal Ilmu Komunikasi Efek, 2024)
This research is driven by the urgent need to understand how effective communication approaches can contribute to the success of educational programs for street children, a group often neglected in the formal education system. Street children face various social and economic challenges that hinder their access to quality education. Therefore, understanding the factors that encourage their involvement in learning programs is a crucial step toward addressing educational inequality. In this study, social exchange theory is used as a framework to assess how interactions and social relationships between educators and street children can create a conducive learning environment. The number of street children showing the success of the Komunitas Peduli Anak Jalanan (KPAJ) in regularly mentoring around 170 street children. This research uses a qualitative descriptive approach with data collected through observation, interviews, and documentation. The research findings indicate that there are five principles of effective communication: Respect is fundamental in this approach, as children feel respected as individuals with voices and rights; Empathy involves community members striving to understand the feelings, experiences, and perspectives of street children; Audible entails the use of a voice that can be clearly heard and understood by the children; Clarity refers to the ability to convey messages clearly and understandably, which is key to building meaningful and productive relationships; and Humility creates an environment that empowers street children to feel heard and valued. Keywords : Communication, Effective Learning, Street Children